Leveraging Social Networking for Talent Management: An Exploratory Study of Indian Firms. (5th June 2017) - Nayak, Sunanda; Bhatnagar, Jyotsna; Budhwar, Pawan
Abstract : Utilizing the social capital and social network theories, this research explores and highlights how social networking has been strategically utilized as an effective tool by organizations for employer branding and innovative talent acquisition strategies in India. Qualitative data from 78 semistructured interviews with human resources (HR) professionals of information technology (IT), information technology–enabled services (ITeS), and talent acquisition organizations confirm the growing utilization of social networking sites (SNSs) as part of the organizational HR strategy for employer branding and talent sourcing, acquisition and retention, and reinforcing stronger relationship with their employees. The study contributes to the fields of talent management and social networks and has several key implications for practitioners regarding the usefulness of SNSs to organizational branding, talent management, and retention. © 2017 Wiley Periodicals, Inc .